(3GdKeQGJ aj CMcGe GdGjGJs
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg GdMce GdKGfi hgh PcQ Gddg JYGdi aEf GdMce hPdc jchf HGdbdH hGddSGf s
(3BNQgG (B:s
(3ajchf Pdc SHHkG ddEeJfGY Yf GLGHJc hai gPG Odjd Ydi Cf ef jUOQ ddEQTGO jJdhg ShQI GdQYO s
(3HgG fXGe GdJYbjHIs
(3HgG CKGQ JeRjbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI ebQhAI ef YGde eYQha (B: (3LeGd GdOjf GdbGSei (B1322(3SfIs
Keywords: (3GdJaSjQ hYdhe GdbQBfs